2012
DOI: 10.1002/mpr.1370
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monetary and social rewards on task performance in children and adolescents: Liking is not enough

Abstract: Introduction:The current study compared the effects of reward anticipation on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…This finding is only partially consistent with studies of monetary or social rewards in adolescents, which typically show an increase in accuracy on higher value trials (Demurie et al, 2012). Moreover, previous studies in adolescents (Demurie et al, 2012) and adults (Rademacher et al, 2010; Spreckelmeyer et al, 2009; Stern et al, 2011) have also shown that reaction times become faster with increasing reward intensity. Our lack of accuracy and reaction time differences may suggest that a larger monetary discrepancy between high- and low-value trials is necessary to differentially motivate such a heterogeneous population of adolescents.…”
Section: Discussionsupporting
confidence: 67%
“…This finding is only partially consistent with studies of monetary or social rewards in adolescents, which typically show an increase in accuracy on higher value trials (Demurie et al, 2012). Moreover, previous studies in adolescents (Demurie et al, 2012) and adults (Rademacher et al, 2010; Spreckelmeyer et al, 2009; Stern et al, 2011) have also shown that reaction times become faster with increasing reward intensity. Our lack of accuracy and reaction time differences may suggest that a larger monetary discrepancy between high- and low-value trials is necessary to differentially motivate such a heterogeneous population of adolescents.…”
Section: Discussionsupporting
confidence: 67%
“…Material rewards (e.g., money, food) and social rewards (e.g., a smiling face, positive feedback; Demurie, Roeyers, Baeyens & Sonuga-Barke, 2012;Ethridge et al, 2017;Foulkes, Viding, Mccrory & Neumann, 2014) may inspire two different forms of extrinsic motivation. They represent two fundamentally different mechanisms of human motivation (Hansen, Smith & Hansen, 2002;Hussain, Shah & Raza, 2012) and have different effects on human behaviors (Alfandi & Alkahsawneh, 2014;Erbasi & Arat, 2012;Kohls, Peltzer, Herpertz-Dahlmann & Konrad, 2009;Saqib, Abrar, Sabir, Bashir & Baig, 2015;Waqas & Saleem, 2014).…”
Section: Materials and Social Rewardsmentioning
confidence: 99%
“…Sixth, one should note that self-reported attitudes towards motivational factors do not necessarily relate to the reinforcing power of these factors; that is, we cannot be sure that these factors are actually capable of influencing behaviour and increasing performance (Demurie et al, 2012). This engagement-performance dissociation might be in line with our result that individuals with internalizing problems (especially peer problems) report to be triggered by social evaluation to engage themselves more, but at the same time seem to exhibit decreased performance in social evaluative contexts (Caouette et al, 2014;Levinson et al, 2014;Stein et al, 2001;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The following themes were identified through thematic analyses (Braun & Clarke, ) of semistructured interviews: (a) achieving a sense of togetherness, (b) feeling competent, (c) needing variation, (d) gaining pleasure from applying effort to achieve a goal, (e) valuing social reinforcement, (f) desiring to be absorbed/to forget problems, (g feeling free and independent, (h) attaining material reinforcement, and (i) enjoying bodily stimulation. These themes provide information on the attractiveness (or likability) of activities (including tasks) as a function of their characteristics, but not on the way in which these task elements might be able to influence motivation to perform the task (Demurie, Roeyers, Baeyens, & Sonuga‐Barke, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation